2022
DOI: 10.3390/cells11060981
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characterization of Portuguese Patients with Hereditary Cerebellar Ataxia

Abstract: Hereditary cerebellar ataxia (HCA) comprises a clinical and genetic heterogeneous group of neurodegenerative disorders characterized by incoordination of movement, speech, and unsteady gait. In this study, we performed whole-exome sequencing (WES) in 19 families with HCA and presumed autosomal recessive (AR) inheritance, to identify the causal genes. A phenotypic classification was performed, considering the main clinical syndromes: spastic ataxia, ataxia and neuropathy, ataxia and oculomotor apraxia (AOA), at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 112 publications
(166 reference statements)
0
7
0
Order By: Relevance
“…On review of the latest literature in the EA, published since the closing date of our initial systematic literature review (April 2021–June 2022), we identified a total of nine related articles (Table S4). These reported on 10 patients with novel variants in the CACNA1A [19–29]. In a case report of CACNA1A ‐related EA, dalfampridine 0.3 mg/kg was shown to resolve falls that had been unresponsive to acetazolamide (treatment was delayed due to insufficient literature on the topic) [30].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…On review of the latest literature in the EA, published since the closing date of our initial systematic literature review (April 2021–June 2022), we identified a total of nine related articles (Table S4). These reported on 10 patients with novel variants in the CACNA1A [19–29]. In a case report of CACNA1A ‐related EA, dalfampridine 0.3 mg/kg was shown to resolve falls that had been unresponsive to acetazolamide (treatment was delayed due to insufficient literature on the topic) [30].…”
Section: Resultsmentioning
confidence: 99%
“…Our review of the latest literature (April 2021–June 2022) revealed a total of two related articles (Table S4). These were reported on two patients with novel variants in the PDHA1 gene [19–29].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…KIF1C-mediated transport to the cilium was proposed to involve a physical interaction with ASAP1, an ARF GTPase-activating protein serving as a scaffold protein to regulate ARF4, RAB8/RAB11-mediated ciliary receptor targeting [ 54 ]. Several studies have identified patients carrying mutations in the KIF1C gene as suffering from hereditary spastic paraparesis, a disorder characterized by spasticity predominantly in the lower limb that could be associated with cerebellar ataxia and upper cervical atrophy [ 6 , 7 , 8 , 55 ]. None of these studies investigated potential defects in ciliogenesis.…”
Section: Ga Related Proteins Necessary For Normal Ciliogenesis/ciliar...mentioning
confidence: 99%
“…Indeed, mutations in multiple members of the kinesin family have been implicated in causing axonopathy phenotypes, including conventional kinesin / kinesin-1 ( KIF5A – spastic paraplegia type 10 / #604187; KIF5C – complex cortical dysplasia with other brain malformations type 2 / #615282; KLC2 - spastic paraplegia, optic atrophy, and neuropathy / #609541), kinesin-3 ( KIF1A - hereditary sensory neuropathy type IIC / #614213 and spastic paraplegia type 30 / #610357; KIF1B - Charcot-Marie-Tooth disease, axonal, type 2a1 / #118210; KIF1C - Spastic ataxia type 2 / #611302), and kinesin-11 ( KIF26B - autosomal dominant spinocerebellar ataxia and pontocerebellar hypoplasia with arthrogryposis) (Kalantari and Filges 2020). Mutations in the kinesin-3 gene KIF1C have been shown to cause autosomal recessive HSP complicated by cerebellar involvement (Caballero Oteyza et al 2014; Dor et al 2014; Yucel-Yilmaz et al 2018; Marchionni et al 2019; Santos et al 2022). Mutation types observed in patients with HSP-KIF1C include missense variants in the kinesin-3 motor domain as well as truncating mutations scattered throughout the open reading frame and thus suggest loss of motor function as the relevant disease mechanism.…”
Section: Introductionmentioning
confidence: 99%